ANALISIS PROSES PELAYANAN PENDAFTARAN PASIEN DI PUSKESMAS JATISRONO I KABUPATEN WONOGIRI - Nurul Balqis Shofiana; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2019)
Health care for the people in Indonesia is through the Puskesmas. The registration unit is a place that is part of the service provided by the officer. Puskesmas Jatisrono I is a health care center in Wonogiri District with the main accreditation rating in the District, but there are still problems with a long waiting time. This study aims to analyze the causes of discomfort in the service process. This research is a qualitative study with indepth interviews with 7 informants. The results of the research on input variables are still greatly reduced registration service personnel, and infrastructure facilities. SOP registration services at the puskesmas are available, but repairs need to be done. The converting process variable that still serves patients is still longer (more than 10 minutes) the standard is 5 minutes, the incompleteness that is done by the patient to be hampered. Suggestions for Puskesmas are socializing for patients about the completeness of the folder, placing banners containing information needed for registration, and Customer Service (CS) on the front to check the completeness of the patient’s folders. Registration unit must research about waiting time using queuing theory.